FENOMENA KOMUNIKASI PRIA BISEKSUAL DI KOTA PEKANBARU - Rizka Nofitri; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Sexual deviation bisexual become a phenomenon that thriving nowadays and many found in men. Even they start bold open with growing the news LGBT that equal rights openly. Until now, the phenomenon bisexual is developing marked by increasing the number of HIV/AIDS as a factor because orientation bisexual and already long spread in GaYa Nusantara bulettin that gives the LGBT information in Pekanbaru. Research aims to understand motives, puport, experience communication man bisexual in Pekanbaru. This research uses the method the qualitative study with the approach phenomenology. The subject of study consisting of five men bisexual in pekanbaru were chosen in using a technique snowball. Using a technique study this data collection in-depth interviews, observation, and research documentation. To reach the validity of data in this research, researcher used extension data and triangulation. The results of this research showed first, motives man bisexual in pekanbaru consisting of a motive (because motive) is the impulse psychic, satisfaction born inner, sensation its own, and trying . While motive ( in order to motive) is heterosesksual, remain bisexual, and recognized by citizen. Second, purport given man bisexual against her namely shame and sinful act, nonessentials regret and self who receives fate. Third, communication experience categorized into two experiences that are fun of a favorable acceptance of the family, affection and attention obtained of their pair, the absence of discrimination and there is a support. And communication experience unpleasant of allusion and reproach of the family, the threat in conflict romance and scorn and shame of friendship environment.   Keyword : phenomenon ,bIxesual, motive, meaning, communication experience